Preferences and decisions with regard to hiring fresh graduates in selected banking institutions in Iloilo City - Mendame, Jallice Kristel; Pedalezo, Kristine; Villasoto, Sharon Mae. (2005)
This study entitled "Preferences and decisions with regard to hiring fresh graduates in selected banking institutions in Iloilo City" aimed to determine the hiring preferences of selected banking institutions in terms of an applicant's school background, competencies and training. Aside from that,it also aspires to describe the hring decisions of selected banking institutions in terms of the nature of work they usually offer for newly hired fresh graduate employees and the employment status of their hired applicants. A descriptive method of research was employed in this study using a survey questionnaire as a gathering instrument. Frequency count, percentage and ranking were the statistical tools used in this study to determine the hiring preferences and decisions of selected banking institutions in Iloilo City. With the use of judgmental sampling, eight managers from eight banking institutions - UCPB, DBP, PNB, BPI, Landbank of the Philippines, Banco de Oro, Equitable PCI Bank, Metrobank-served as respondents of this study. The results revealed that the respondents' hiring preferences are influenced by the applicant's school background. The ranking shows that the top favored University in the city is the University of the Philippines in the Visayas, which was ranked first, followed by the Central Philippine University that was ranked second, followed by the University of San Agustin, Saint Paul University, University of Iloilo, Iloilo Doctor's College and John B. Lacson Colleges Foundation respectively. In terms of the respondents hiring decisions, most banking institutions place newly hired fresh graduate applicants in front liner positions such that of a teller, new account personnel and office staffs. Furthermore, they are given a six month probationary period, before they would qualify as regulal employees. Most banking institutions then offer newly hired fresh graduate employees a monthly compensation ranging from 7,000-8,000Php. With the following findings, this study concluded that hiring preferences of selected banking institutions are influenced by an applicant's school background, competencies and trainings. For hiring decisions, banks give a six-month probationary period before an employee will be regularly hired as frontline personnel. However, a monthly salary of 7,000-8,000 a month is insufficient for an employee to live up to the standard cost of living. This study therefore recommends that banks should consider having job fares on their preferred Universities, provide preliminary examination during hiring to determine their applicants' competencies. It is also suggested that banking institutions should raise employee's monthly compensation to 9.750 Php for employees to live up to the standard and to attract competent applicants. Further research studies similar to this are also recommended.
Undergraduate Research (Mgt 200 - Management Research). -- Iloilo City : UPV-CM, October 2005.